PENGARUH SINKRONISASI PERENCANAAN DAN PENGANGGARAN, KUALITAS SUMBER DAYA MANUSIA DAN KOMITMEN ORGANISASI TERHADAP KINERJA PEMERINTAH DAERAH KABUPATEN BENGKULU TENGAH - Fadillah, Adi Yanuar; Aziza, Nurna; Martiah, Lisa (UNIB Press, 2020)
The purpose of this research is to know the influence of synchronism of planning and budgeting, human resources quality, and organizational commitment on government of performance of Central Bengkulu Regency. The samples of this study are 117 respondents. Data analysis in this research use descriptive statistic and multiple regression analysis. The results showed that: (1) the synchronism of planning and budgeting has a positive influence on government of performance of Central Bengkulu Regency; (2) the human resources quality has a positive influence on government of performance of Central Bengkulu Regency; and (3) the organizational commitment has a positive influence on government of performance of Central Bengkulu Regency.